Historian in the Grip of Non-Contradiction. Once More on the Cultural Uncertainty Principle (Appendix to the Reply) - Wrzosek, Wojciech (Sensus Historiae, 2024)
The author refers to the reception and criticism of the idea of epistemology of history that he has been promoting for many years, in particular the category of historiographical metaphor. The essence involves two sub-categories: cultural imputation (in the form of historiographical imputation) and the cultural uncertainty principle. The problems analysed belong to the epistemological dilemmas of history.